“Translated by Arkadiy Kots”: Weaponization, Consecration, Monumentalization and Reincarnation of the Russian “Internationale” - Boulogne, Pieter (chronotopos – A Journal of Translation History, 2025)
The impact of Arkadiy Kots as the translator of “L’Internationale” on Russian society is easy to underestimate. His Russian song translation, which emerged as a product of the counterculture, was first weaponized by Lenin to motivate workers to engage in the Russian Revolution. Then, it became the object of consecration: it was made the first anthem of the Soviet Union. However, with the passing of time, the song became an ideological and diplomatic issue, which under Stalin was solved by its monumentalization. As an established monument, Kots’s translation remained a fixture in Soviet culture until the very collapse of the empire. It is obvious that the failure of the Soviet experiment heavily damaged Kots’s cultural value. Nevertheless, his song translation remains present in post-Soviet Russia as the anthem of the Communist Party of the Russian Federation. At the same time, Kots also serves as an inspiration for the protest band that under his name has translated “L’Estaca”, which, as the most popular protest song of our time, could be seen as a reincarnation of “L’Internationale”.